TRANSFORMASI NILAI NILAI KEARIFAN LOKAL (LOCAL GENIUS) DALAM PROSES PEMBELAJARAN SEBAGAI UPAYA PEMBENTUKAN KARAKTER BANGSA PADA SMA SE-KABUPATEN SIMEULUE - Ali, Hasbi (PKn Progresif, 2017)
Lately there has been frequent friction between groups that are only triggered by small things, both among the general public and the educated. Many people worry that if conditions like this continue, it is not impossible that this nation will experience degradation that can threaten the unity and unity of the nation. The transformation of local wisdom values (local genius) in the learning process is needed as an effort to reduce global influence that can damage the character of learners in line with the current modernization. However, the learning of religion, manners, and PPKn has not been able to maximally shape the character of learners. Therefore, the need for character education as a form of mental revolution of learners with the value of local wisdom.